MOLECULAR DETECTION OF PARVOVIRUS FROM SERA OF CHILDREN WITH RASH RED ILLNESS - Haider H. Mitab (Scholar Express Journals, 2022)
A parvovirus infection is distinguished by a bright red rash on the cheeks. Human parvovirus B19 infection is a typical and contagious illness in children.
Keywords: Rash; parvovirus; B19; gender